Related Factors of Social Personal Task Achievement of Preschool Children - Musyafirah Mutia; Andriani Andriani; Hapsah Hapsah (Indonesian Contemporary Nursing Journal, 2016)
Introduction: In preschool age, the social aspects of children personal development can be influenced by some factors. They are parenting parents, environment conditions, and peers. The unfulfilled social personal development in preschool children will cause children being passive, fearful, and less initiative. This study aimed to identify factors associated with achievements of social personal task in children of  TK Al-Jabar at Barugae village Bulukumpa district Bulukumba regency. Method: Descriptive analytic with cross sectional approach, for 47 respondents. Result: Some factors like parenting parents (p=0.015), environment condition (0,026), are related to the achievements of social personal tasks of preschool children in TK Al-Jabar at Barugae village. While Peers (p=0,191) do not have a correlation to the achievement of social personal task of preschool children in TK Al-Jabar at Barugae village Bulukumpa district Bulukumba regency. Conclusion: There is a relationship between parenting parents with personal tasks of social achievement. Although, the relation of two variables is moderate. Therefore,  involvement of all parties:parents, communities, teachers and the nursing professions in this case needs to be actively developed in promotive and preventive efforts for achieving the social personal task of preschool children